Bridging Classroom Realities and School Governance: The Roles and Responsibilities of Teachers within South African SMTs during the Digital Era - Tsakaria Netshisumbewa; Takalani Samuel Mashau; Matodzi Grace Muremela (International Journal of Educational Qualitative Quantitative Research, 2026)
In the contemporary digital era, effective school leadership increasingly depends on collaborative approaches that can rapidly translate dynamic classroom data into responsive institutional strategies. Grounded in Distributed Leadership Theory, this study explores the evolving roles and responsibilities of teachers within School Management Teams (SMTs) in South African schools. A qualitative research design was employed, utilizing semi-structured interviews to gather in-depth insights from school principals, deputy principals, and department heads (DHs). Thematic analysis reveals that teachers serve as a critical bridge between micro-level classroom realities and macro-level school governance. Specifically, teachers enhance SMTs decision-making by transforming classroom-based insights and student assessment data into actionable school policies. Furthermore, teachers drive instructional adaptation through data-driven interventions, personalized learning support, and proactive classroom management, which directly foster student resilience and academic achievement. However, the study highlights that maximizing teacher leadership in this digital climate requires sustained, collaborative professional development to overcome persistent institutional resource constraints. These findings underscore the critical need for educational authorities to foster inclusive, technologically-adaptive leadership practices that recognize teachers as legitimate co-constructors of school improvement and learner success. Concurrently, this study offers a significant empirical contribution by conceptualising a modern framework of distributed governance that links immediate pedagogical datasets with strategic school administration in post-apartheid developing contexts.